Multicomponent synthesis and photophysical study of novel α,β-unsaturated carbonyl depsipeptides and peptoids - González, Ricelia; Murillo-López, Juliana; Rabanal-León, Walter; Prent-Peñaloza, Luis; Concepción, Odette; Olivares, Pedro; Duarte, Yorley; de la Torre, Alexander F.; Gutiérrez, Margarita; Caballero, Julio (Frontiers in Chemistry, 2023)
Multicomponent reactions were performed to develop novel α,β-unsaturated carbonyl depsipeptides and peptoids incorporating various chromophores such as cinnamic, coumarin, and quinolines. Thus, through the Passerini and Ugi multicomponent reactions (P-3CR and U-4CR), we obtained thirteen depsipeptides and peptoids in moderate to high yield following the established protocol and fundamentally varying the electron-rich carboxylic acid as reactants. UV/Vis spectroscopy was utilized to study the photophysical properties of the newly synthesized compounds. Differences between the carbonyl-substituted chromophores cause differences in electron delocalization that can be captured in the spectra. The near UV regions of all the compounds exhibited strong absorption bands. Compounds P2, P5, U2, U5, and U7 displayed absorption bands in the range of 250–350 nm, absorbing radiation in this broad region of the electromagnetic spectrum. A photostability study for U5 showed that its molecular structure does not change after exposure to UV radiation. Fluorescence analysis showed an incipient emission of U5, while U6 showed blue fluorescence under UV radiation. The photophysical properties and electronic structure were also determined by TD-DFT theoretical study.